A Serious Game to Improve Emotion Regulation in Treatment-Seeking Individuals With Gambling Disorder: A Usability Study - Mena-Moreno, Teresa; Fernández-Aranda, Fernando; Granero, Roser; Munguía, Lucero; Steward, Trevor; López-González, Hibai; del Pino-Gutiérrez, Amparo; Lozano-Madrid, María; Gómez-Peña, Mónica; Moragas, Laura; Giroux, Isabelle; Grall-Bronnec, Marie; et al. (Frontiers in Psychology, 2021)
Background: Serious games have shown positive results in increasing motivation, adherence to treatment and strengthening the therapeutic alliance in multiple psychiatric disorders. In particular, patients with impulse control disorders and other disorders in which the patient suffers from inhibitory control deficits (e.g., behavioral addictions) have been shown to benefit from serious games. Aim: The aim of this study was to describe the characteristics and to evaluate the usability of a new serious videogame, e-Estesia. This serious videogame was designed to improve emotion regulation in patients with gambling disorder (GD). Preliminary results from a pilot sample are also reported. Method: A pilot sample of 26 patients undergoing treatment for GD was recruited (ranging from 22 to 74 years, mean = 41.2 and SD = 12.9; 80.8% men). Participants used e-Estesia on a tablet, which was connected to a thoracic band that sent heart rate (HR) and heart rate variability (HRV) data to the videogame platform in order to provide biofeedback. The System Usability Scale was completed by patients to determine the usability of e-Estesia. Results and Discussion: e-Estesia performed comparatively well for all the explored groups (i.e., sex, age, and online vs. offline gambling: mean usability score = 83.8, SD = 13.1). Around 84.6% of the patients endorsed that it was easy to use. Female patients with GD presented higher HRV during the use of the serious videogame compared to men.